Parasitic intestinal diseases and immune status in adult patients with HIV infection at the Peruvian Naval Medical Center "Cirujano Mayor Santiago Távara" - Vergaray, Silvana (2019)
Objective: To describe the types of parasitic intestinal diseases and the immune status in human immunodeficiency virus-positive (HIV+) patients. Materials and methods: A descriptive, comparative and retrospective study was carried out through the selection of 81 medical records from the Infectious Disease Service of the Naval Medical Center "Cirujano Mayor Santiago Távara", with the authorization of the pertinent authorities. Said medical records included the only inclusion criterion considered in the research: the diagnosis of HIV infection. The following data was obtained: results from a copro-parasitological examination and a flow cytometry for CD4 T lymphocyte count, presence or absence of gastrointestinal symptoms, and participation in the Highly Active Antiretroviral Therapy (HAART) program or the conventional antiretroviral treatment program. Results: Thirty-seven percent (37 %) of the patients presented parasitic intestinal diseases, with Entamoeba coli being the most frequently observed parasite (20 %), which is not pathogenic for humans. Among the pathogens, Isospora belli (15.6 %), Giardia lamblia (15.6 %), Blastocystis hominis (11.2 %) and Cryptosporidium sp. (11.2 %) were found. Thirty-two point one percent (32.1 %) of the subjects had diarrhea, while 67.9 % were asymptomatic. In the asymptomatic group, the average CD4 cell count was 280 cells/μL, while in those with diarrhea it was 195 cells/μL. Conclusions: Enteroparasites Isospora belli, Cyclospora cayetanensis and Blastocystis hominis are most frequently found at CD4 cell counts <199 cells/uL. Non-pathogenic parasites Entamoeba coli, Endolimax nana, Trichomonas hominis and Chilomastix mesnili are most frequently found in patients with CD4 cell counts >200 cells/μL.